2010
DOI: 10.3748/wjg.v16.i22.2832
|View full text |Cite
|
Sign up to set email alerts
|

Impaction of a lithotripsy basket during endoscopic lithotomy of a common bile duct stone

Abstract: The treatments for common bile duct (CBD) stones are being continually developed. Impaction of the lithotripsy basket during endoscopic removal of CBD stones was seen in 5.9% patients. We report the case of a 66-year-old woman who underwent surgery for the removal of an impacted biliary basket. She was admitted to our hospital with a complaint of right upper abdominal pain. Magnetic resonance cholangiopancreatography revealed a CBD stone (20 mm x 15 mm). We diagnosed her with choledocholithiasis and performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 14 publications
0
19
0
1
Order By: Relevance
“…Stones that are 2 cm in diameter or larger are prone to becoming embedded in the wire loops during removal [1]. In addition, cholecystitis and/or cholangitis may induce inflammatory changes in the CBD, leading to stiffness and deformation of the duct, which reduces the working space between the stone and the wall of the CBD [2]. Once distortion of the Dormia basket, similar to the that described herein (see • " Fig.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…Stones that are 2 cm in diameter or larger are prone to becoming embedded in the wire loops during removal [1]. In addition, cholecystitis and/or cholangitis may induce inflammatory changes in the CBD, leading to stiffness and deformation of the duct, which reduces the working space between the stone and the wall of the CBD [2]. Once distortion of the Dormia basket, similar to the that described herein (see • " Fig.…”
mentioning
confidence: 55%
“…1), has occurred, impaction or rupture becomes very likely, and it may be better to consider alternative ways of widening of the papilla or fragmenting the stone. In some cases, use of a second basket or shockwave lithotripsy can help remove or fragment the entrapped stone [3,4], but once the basket be- Cases and Techniques Library (CTL) E20 comes severed, with its opened loops facing downwards, manipulation from below is likely impossible and dangerous, and its removal through open choledochotomy may become mandatory [2].…”
mentioning
confidence: 99%
“…The main factor responsible for the impaction of the basket and as described in the cases we report, is the large size of the stones (>15–20 mm). Some authors have reported that the presence of a stone larger than 20 mm in size as a contraindication to performing ERCP [ 6 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Один из актуальных вопросов -извлечение из холедоха крупных камней (>20 мм). В литературе описаны методы их дробления внутри холедоха посредством интракорпоральной электрогидравлической литотрипсии и дробления корзиной [2,7]. B. Vladimirov приводит данные об успешности литотрипсии у 171 из 236 больных с осложнениями в 11% случаев.…”
Section: Rationale For Effectiveness Of a New Methods Of Radial Sphincunclassified